Transition of care from the emergency department to skilled nursing facility: Retrospective case‐control study - Alec P. Tolentino; Kelli S. Gaus; Yingqiu Gao; Kevin J Chronowski; Jane Helen Brice; Eugenia B. Quackenbush (Journal of the American College of Emergency Physicians Open)
Abstract Objective The primary objective of this study is to describe associations between emergency department (ED)‐to‐skilled nursing facility (SNF) transition and ED length‐of‐stay (LOS). The secondary objective is to explore how social determinants of health (SDOH) influence ED‐to‐SNF transition visit parameters. In 2020, The Centers for Medicare & Medicaid Services issued the “COVID‐19 Emergency Declaration Blanket Waivers for Health Care Providers” eliminating the requirement of a 3‐day qualifying hospital stay before SNF placement. The waiver allowed ED patients to be transitioned directly to an SNF from the ED. Methods We conducted a descriptive retrospective case‐control study of adult patients who sought care in the University of North Carolina Hospitals (UNCH) ED between March 1, 2020, and March 1, 2022, lived in a non‐SNF residence before their ED visit, and were transitioned directly to an SNF from the ED (n1 = 27), compared with a group seen in the ED and admitted to hospital for SNF placement (n2 = 54). Results The ED‐to‐SNF group experienced a significantly longer ED LOS compared to the ED‐to‐Inpatient‐to‐SNF group: 72.8 hours (95% confidence interval [CI], 59.2–86.4) compared to 14.5 hours (95% CI, 12.1–16.9). We found no significant differences in SDOH between the ED‐to‐SNF group and the ED‐to‐Inpatient‐to‐SNF group. Conclusion Patients who transition from the ED to an SNF experience long ED stays that may adversely affect health and well‐being. Transitioning directly from the ED to an SNF may contribute to ED boarding and overcrowding.